Cell biology and genetics of root hair formation in Arabidopsis thaliana. - Ryan, E; Steer, M; Dolan, L (2001)
In this review we integrate the information available on the cell biology of root hair formation with recent findings from the analysis of root hair mutants of Arabidopsis thaliana. The mature Arabidopsis root epidermis consists of root-hair-producing cells and non-root-hair-producing cells. Root hair growth begins with a swelling of the outer epidermal wall. It has been postulated that this is due to a pH-mediated localised cell wall loosening. From the bulge a single root hair emerges which grows by tip growth. The root hair tip consists of a vesicle-rich zone and an organelle-rich subapical zone. The vesicles supply new plasma membrane and cell wall material for elongation. The cytoskeleton and its associated regulatory proteins such as profilin and spectrin are proposed to be involved in the targeting of vesicles. Ca2+ influxes and gradients are present in hair tips, but their function is still unclear. Mutants have been isolated with lesions in various parts of the root hair developmental pathway from bulge identity and initiation to control of tip diameter and extent and polarity of elongation.